SEMIOTIC ANALYSIS OF PEIRCE AND SAUSSURE IN BUILDING THE VISUAL MEANING OF THE SISSCA LOGO (SAWAHLUNTO INTERNATIONAL SONGKET SILUNGKANG CARNAVAL) - Rahmat Reza Hidayat; Asril; Dede Pramayoza; Sahrul N (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to analyze the SISSCA (Sawahlunto International Songket Silungkang Carnival) logo through the semiotic approach proposed by Charles Sanders Peirce and Ferdinand de Saussure. Method: The research employs a qualitative method, gathering data through visual observation, documentation, and in-depth interviews with the event organizers and several carnival attendees. Results: The results of the analysis indicate that the SISSCA logo effectively constructs complex visual meanings through a combination of icons, indices, symbols, and signifier-signified relationships. These elements not only shape visual identity but also function as a powerful communication medium in conveying local cultural values and institutional image. Therefore, this logo serves not only as a recognition symbol but also as a symbolic representation of Sawahlunto's cultural richness and international carnival spirit. Novelty: The primary focus of the analysis is on the visual elements within the logo, such as distinctive buildings, feathers, colors, and typography, which are examined as signs carrying cultural, aesthetic, and institutional identity meanings. These findings offer valuable insights for graphic designers and marketing practitioners in understanding the significant role of semiotics in creating brand images that are rich in meaning and possess profound symbolic allure.